2007
DOI: 10.1029/2006gl028090
|View full text |Cite
|
Sign up to set email alerts
|

Ice‐core record of methyl chloride over the last glacial–Holocene climate change

Abstract: Methyl chloride (CH3Cl) concentration was measured in air trapped in a deep ice core from Dome Fuji, Antarctica covering the last glacial–present interglacial (Holocene) change. The record shows that the CH3Cl concentration was relatively constant, being similar to the present levels, during the pre‐industrial Holocene. In contrast, the CH3Cl concentration was significantly high and variable in the last glacial period, possibly due to impurity‐related production of CH3Cl in ice sheet. Under the assumption that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2007
2007
2025
2025

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 34 publications
1
12
0
Order By: Relevance
“…Measurements of CH 3 Cl in a shallow ice core from Siple Dome, Antarctica covering the past 300 years suggest that the twentieth century increase was part of a more complex, preexisting pattern of variability [ Aydin et al , 2004]. Limited measurements of CH3C1 in Deep ice from Dome Fuji, Antarctica [ Saito et al , 2007] imply that atmospheric levels were relatively constant throughout the Holocene. The firn air and ice measurements published to date suggest that the Antarctic ice archive contains a record of atmospheric CH 3 Cl that is not severely overprinted by local effects or in situ production and loss.…”
Section: Introductionmentioning
confidence: 99%
“…Measurements of CH 3 Cl in a shallow ice core from Siple Dome, Antarctica covering the past 300 years suggest that the twentieth century increase was part of a more complex, preexisting pattern of variability [ Aydin et al , 2004]. Limited measurements of CH3C1 in Deep ice from Dome Fuji, Antarctica [ Saito et al , 2007] imply that atmospheric levels were relatively constant throughout the Holocene. The firn air and ice measurements published to date suggest that the Antarctic ice archive contains a record of atmospheric CH 3 Cl that is not severely overprinted by local effects or in situ production and loss.…”
Section: Introductionmentioning
confidence: 99%
“…During last glacial period (33–65 kyr BP) about 50% of the Ca +2 was of terrestrial origin. Saito et al [2007] did not observe a correlation between dust levels and CH 3 Cl during the Holocene when Ca +2 levels were below 0.6 μ mol l −1 . This may suggest a threshold in dust input above which in situ production of CH 3 Cl becomes detectable above the atmospheric background.…”
Section: Resultsmentioning
confidence: 99%
“…By contrast, the Siple Dome glacial data prior to the LGM and the glacial/interglacial transition (33 -65 kyr BP) are comparable to, or slightly lower than Holocene levels, with a mean of 456 ± 46 ppt. Saito et al [2007] demonstrated a strong positive correlation between the glacial CH 3 Cl levels at Dome Fuji and the levels of Ca +2 in the enclosing ice. This is convincing evidence that there is ''excess'' CH 3 Cl in the Dome Fuji core, resulting from in situ production, most likely related to chemical or biological reactions involving terrigenous dust and/or associated organic material.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, firn air and ice core studies have been used to examine the atmospheric variability of less abundant trace gases such as methyl chloride, methyl bromide, and carbonyl sulfide Butler et al, 1999;Saito et al, 2007;Saltzman et al, 2008;Sturges et al, 2001a, b;Trudinger et al, 2004;Williams et al, 2007). These measurements, which can potentially be extended to a range of low-level trace gases, allow for examination of the natural variability in atmospheric levels of these compounds as well as the influence of human activities on the trace gas composition of the atmosphere.…”
Section: Introductionmentioning
confidence: 99%